Application of acceptance commitment therapy in maintenance hemodialysis patients (接纳承诺疗法在维持性血液透析患者中的应用) - GENG Zaixiang (耿在香); CAO Hongmei (曹红梅) (Association of Integrative Nursing, 2021)
Objective To explore the effect of acceptance commitment therapy (ACT) on anxiety, depression and self-management ability of maintenance hemodialysis (MHD) patients. Methods Totally 70 MHD patients admitted to the Hemodialysis Center of Affiliated Hospital of Yangzhou University from June to December 2019 were selected as the research objects and randomly divided into control group (n=35) and study group (n=35). The control group received routine nursing, and the study group received act intervention. After 8 weeks, the scores of Self-rating Depression Scale and Self-rating Anxiety Scale, self-management ability were compared between the two groups before and after nursing. Results After 8 weeks of intervention, scores of SDS and SAS in the study group were lower than those before the intervention (P < 0. 05), and scores of SDS and SAS in the study group were lower than those in the control group (P < 0. 05). After 8 weeks of intervention, the scores of self-management ability in the study group were higher than those before the intervention (P < 0. 05), and the scores of self-management ability in the study group were higher than those in the control group (P < 0. 05). Conclusion ACT can relieve the anxiety and depression status of MHD patients, improve their self-management ability and quality of life. (目的 探讨接纳承诺疗法(ACT)对维持性血液透析(MHD)患者焦虑、抑郁情绪及自我管理能力的影响。方法 选取2019年6月～12月收治的70例MHD患者作为研究对象, 采用随机数字表法分为对照组和研究组, 各35例。对照组实施常规护理, 研究组在对照组基础上进行ACT干预。比较2组患者干预前后抑郁和焦虑评分、自我管理能力评分。结果 干预8周后, 研究组焦虑自评量表(SAS)、抑郁自评量表(SDS)得分较干预前显著降低(P＜0. 05), 且评分低于同期对照组, 差异有统计学意义(P＜0. 05)。干预8周后, 研究组患者自我管理水平各维度得分与干预前比较, 差异有统计学意义(P＜0. 05), 且高于同期对照组评分, 差异有统计学意义(P＜0. 05)。结论 ACT可改善MHD患者焦虑、抑郁情绪, 提高患者的自我管理能力, 有利于提高患者的生存质量。)